2016
DOI: 10.6000/1927-3037.2016.05.04.4
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Screening for Antimicrobial Activity of Some Medicinal Plant Seed Extracts

Abstract: Phytochemical screening (saponins, tannins, steroids, alkaloids, flavonoids, phenols and glycosides) of four medicinal plant seeds (Jatropha curcas, Simmondsia chinensis (Jojoba), Moringa oleifera and Datura metel) extracted by aqueous, ethanol and Folch solvents, were examined for their antimicrobial activity against three types of plant pathogenic fungi namely; Botrytis cinerea, Fusarium oxysporum and Rhizoctonia solani, in addition to four types of bacteria, namely; Bacillus cereus, Staphylococcus aureus, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Moringa oleifera was chosen for this study based on the previous reports that indicated its antifungal and antimicrobial properties effective against various phytopathogens (Emad El Din et al, 2016;Batista et al, 2014;Belay and Sisay, 2014;Díaz Dellavalle et al, 2011). Considering the efficacy of the solvent extracts and the morphological part of the plant used (seeds or leaf), the results on the bioassay showed that organic solvent extracts proved to have high antifungal activity against B. cinerea isolates than the aqueous extract irrespective of the morphological part of the plant used.…”
Section: Discussionmentioning
confidence: 99%
“…Moringa oleifera was chosen for this study based on the previous reports that indicated its antifungal and antimicrobial properties effective against various phytopathogens (Emad El Din et al, 2016;Batista et al, 2014;Belay and Sisay, 2014;Díaz Dellavalle et al, 2011). Considering the efficacy of the solvent extracts and the morphological part of the plant used (seeds or leaf), the results on the bioassay showed that organic solvent extracts proved to have high antifungal activity against B. cinerea isolates than the aqueous extract irrespective of the morphological part of the plant used.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study revealed that three concentrations (S, S/2 and S/4) of castor bean, colocynth, jojoba and moringa oils showed significantly (P ≤ 0.05) inhibitory effect on egg hatch and increased juvenile mortality of M. incognita in vitro. Gomaa et al, 2016;Bello et al, 2019). The inhibitory effect of the tested oils may be attributed to the presence of chemicals with nematicidal effect.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, plants are a source of many active nematicidal compounds and essential oils (Kong et al, 2007). Moreover, a wide variety of plant species, representing 57 families have been shown to have nematicidal compounds such as alkaloids, isothiocyanates, phenols, glycosides, thiophenics, tannins, saponins and fatty acids (Gommes, 1981;Chitwood, 2002 (El-Shrief et al, 2014;Gomaa et al, 2016;Bello et al, 2019). Therefore, the main option of the present research was designed to estimate the nematicidal effect of aqueous commercial seed oils of castor bean, colocynth, jojoba, and moringa on egg hatching and juvenile mortality of M. incognita under in vitro conditions.…”
Section: Introductionmentioning
confidence: 99%